Diseño de un recubrimiento comestible con inulina de agave (Agave americana) y aceite esencial de hierba luisa (Cymbopogon citratus) para la conservación de la frutilla (Fragaria ananassa duch). - Arias Palma, Gabriela Beatriz (2022)
Fruits and vegetables are foods that have a short shelf life, generating large losses during storage, which is why it is becoming increasingly necessary to generate alternatives that improve post-harvest conditions and improve their conservation. The objective of this research is to design an edible coating with agave inulin and lemon verbena essential oil for the preservation of strawberries, for which two concentrations of inulin were evaluated with and without the addition of lemon verbena essential oil. The coating-forming solution was characterized based on its density, viscosity and thickness of the film formed. According to these parameters, the formulation that presented the best physical characteristics is the one that contains 10% agave inulin and 0.1% agave inulin. lemon verbena essential oil, the reported values were viscosity 15927 cP, density 1.078 and film thickness 0.035mm. The edible coating was applied to strawberries that were stored under ambient and refrigeration conditions for 10 days, during which time quality parameters of the strawberries were analyzed. The different formulations of the edible coating based on agave inulin and lemon verbena essential oil applied to strawberries influenced the quality parameters of the fruit. The best treatment was considered T5, which corresponds to 5% of agave inulin, 0.1% of lemon verbena essential oil, since under refrigeration conditions the percentage of weight loss decreased by 53.97%, it presented a minimum variation in the concentration of soluble solids with a value of 10.20 ºBrix at the end of the storage period; and reported an index of fungus affectation of 20% compared to the control.